PENGARUH PENEMPATAN PEGAWAI TERHADAP KINERJA ORGANISASI DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Udaya Madjid (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2017)
This research discuses about effect of the placement officer of organization’s performance Tanggamus Regency DPRD secretariat and how the placement strategy officer. Design in this research using descriptive analysis with quantitative approach, which involved 78 respondents from the Legislative Secretariat officials Tanggamus regency, which is determined by using sampling techniques saturated. While the strategy in the placement of employees using SWOT analysis. From the results of the research revealed that this can influence the performance of employees against the organization secretariat DPRD Tanggamus regency determinan coefficient with a value of (r2) of (0.869)2 or (75.50%) which can meant that the Organization Secretariat Performance Legislative Tanggamus regency influenced by the placement of employees. Strategy in the placement of employees based on the SWOT analysis, namely (1) Develop a system of planning and management of employee career employees based on the needs of the organization, (2) Develop and maintain the Quality of Life work that condition, (3) To re-orientation education and training activities through the identification of Training needs for the organization, (4) To update the analysis of the position, work load analysis and analysis of job placement of employees as a basis. Keywords: performance organizational, placement of employee